Il passer epicureo: Lucrezio nei carmi 2 e 3 di Catullo - Nicola Piacenza (Annali Online dell'Università di Ferrara. Sezione Lettere, 2020)
The aim of this article is to demonstrate that the passer in Catullus’ cc. 2 and 3 is a symbol for the epicurean poet Lucretius. In c. 2 Catullus describes Lucretius’ bond with the epicurean sapientia (the puella) and hopes for himself to achieve peace and quiet in the same way. In c. 3 Catullus celebrates Lucretius’ death. Many evidences show that Catullus, mentioning the sparrow, makes clear allusions to concepts and words used by Lucretius in the De rerum natura. In addition, some wordplays seem to confirm the correctness of the starting hypothesis.